2010
DOI: 10.1074/jbc.m110.117366
|View full text |Cite
|
Sign up to set email alerts
|

PKA-induced Receptor Activator of NF-κB Ligand (RANKL) Expression in Vascular Cells Mediates Osteoclastogenesis but Not Matrix Calcification

Abstract: Vascular calcification is a predictor of cardiovascular mortality and is prevalent in patients with atherosclerosis and chronic renal disease. It resembles skeletal osteogenesis, and many bone cells as well as bone-related factors involved in both formation and resorption have been localized in calcified arteries. Previously, we showed that aortic medial cells undergo osteoblastic differentiation and matrix calcification both spontaneously and in response to PKA agonists. The PKA signaling pathway is also invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 46 publications
2
32
0
1
Order By: Relevance
“…Epidemiological studies show vascular calcification is inversely related to serum RANKL and positively related to serum OPG [1418]. Moreover, some in vitro studies showed that RANKL treatment induced vascular calcification [19, 20], whereas we and others found no effect [21, 22], albeit in different species and culture conditions.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Epidemiological studies show vascular calcification is inversely related to serum RANKL and positively related to serum OPG [1418]. Moreover, some in vitro studies showed that RANKL treatment induced vascular calcification [19, 20], whereas we and others found no effect [21, 22], albeit in different species and culture conditions.…”
Section: Introductionmentioning
confidence: 53%
“…RANKL has been implicated in vascular calcification in some studies [19, 20, 28] but not others [21, 22, 29]. These differences may relate to different model systems and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , SMCs have been reported to express RANKL in response to oxidative stress. In addition, endothelial cells express RANKL in response to inflammatory cytokines, as do activated T-cells[3235]. Other in vitro studies have shown that RANK is expressed on endothelial cells, SMCs and monocytes-macrophages[36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…These cells may be derived from monocytic cells in the circulation that are triggered to undergo osteoclastic differentiation in the calcific milieu of the diseased vascular wall [31]. …”
Section: Sources Of Calcifying Cellsmentioning
confidence: 99%